Neuroscience of Compulsive Eating Behavior - Moore, Catherine F.; Sabino, Valentina; Koob, George F.; Cottone, Pietro (Frontiers in Neuroscience, 2017)
A systematic characterization of compulsivity in pathological forms of eating has been proposed in the context of 3 functional domains: 1) habitual overeating; 2) overeating to relieve a negative emotional state; and 3) overeating despite aversive consequences. In this review, we provide evidence supporting this hypothesis and we differentiate the nascent field of neurocircuits and neurochemical mediators of compulsive eating through their underlying neuropsychobiological processes. A better understanding of the neurobiological mechanisms that lead to compulsive eating behavior can improve behavioral and pharmacological intervention for disorders of pathological eating.